Accuracy of Parallel Periapical Versus Bitewing Radiographs in Determining the Level of Alveolar Bone Crest at the Posterior Area of the Jaws - Samadaei , Mahdis; Behnampour, Nasser; Ahmadinia, Amir reza (Journal of Dental School, 2023)
Objectives Periodontal clinical parameters are highly sensitive for the assessment of bone resorption, while radiographic images are highly specific. Two-dimensional parallel periapical (PA) and bitewing (BW) intraoral radiographs are used as adjuvant methods to assess bone resorption in periodontal diseases. The present study aimed to compare the efficacy of PA and BW radiographs in assessing marginal bone level. Methods This cross-sectional study was conducted on 77 (52 females and 25 males) subjects with a mean age of 40.12±14.9 years with chronic periodontitis. Parallel PA and BW radiographs of patients, who required periodontal flap surgery or crown lengthening, were acquired, and evaluated. The distance between the alveolar bone crest (ABC) and the cemento-enamel junction (CEJ) was determined during surgery using the Williams probe. The same distance was measured in proximal areas on intraoral radiographs using Romexis Version 11.4. To evaluate intra-observer agreement, three observers re-evaluated the radiographs after a minimum of 1 week. Intra-class correlation coefficient (ICC) was applied to evaluate the inter- and intra-observer agreement. Data were analyzed using the Shapiro-Wilk test and paired t-test. Results According to the results, the mean distance between the CEJ and ABC was 4.61±1.22 mm, and the mean distance on the PA and BW radiographs was 4.20±1.23 (P<0.001) and 4.02±1.06 mm (P<0.001), respectively. PA radiography was more accurate than BW radiography, although the difference was insignificant (P=0.182). The mean ICC value of the inter-observer agreement was 0.88 for BW and 0.87 for PA radiographs. The mean intra-observer agreement was 0.97 and 0.95 for BW and PA radiographs, respectively. Conclusion The accuracy of PA radiography was higher than BW radiography. However, there was no significant difference regarding the accuracy of these two techniques in determining the level of ABC in the posterior area of the jaws.